(untitled) (GIST – Education and Learning Research Journal, 2021)
This study was designed to investigate the impact of visual mnemonic technique on young and adult Iranian English learnersʹ vocabulary learning. The current study followed quasi- experimental design. 48 female students were selected based on their performance on Quick Placement Test. The purpose of the QPT was to homogenize the participants based on their proficiency level. The participants were divided into four groups, two experimental and two control groups. Each group consisted of 12 participants. Prior to the treatment, the participants of both groups were given a pretest to determine the knowledge of vocabulary in the experimental and control groups. Then the experimental groups received the visual mnemonic technique for 8 sessions. The control groups went through a traditional method of teaching vocabulary. After 8 sessions, a posttest was administered to all groups. Two-way between-groups ANOVA was run to the results of the vocabulary tests to look at the individual and joint effect of the independent variables on dependent variable. It was concluded that mnemonic technique significantly affected Iranian pre- intermediate EFL learners’ vocabulary leaning. The study exhibited that the experimental group who received instruction on mnemonic technique outperformed their counterparts in posttest of vocabulary. However, the differences between the effects of mnemonic technique for young and adult learners who received the specific treatment were not statistically significant (P≥ .05).